Habitual daily walking of at least 8,000 steps increases fecal acetate but not muscle mass in healthy young adults: A 3-month intervention study - Morita, Emiko; Ando, Suguru; Fukuyama , Yumi; Kikuchi, Yui; Kumabe, Sho; Yamashina, Yoshihiro (Health Promotion & Physical Activity, 2025)
Purpose: Physical activity not only benefits musculoskeletal health but also influences gut microbiota and its metabolites, including short-chain fatty acids (SCFAs). Butyrate has been linked to muscle protein synthesis and the prevention of muscle loss; however, evidence in healthy young adults remains limited. This study investigated the effects of a 12-week increase in daily walking on fecal SCFA concentrations and muscle mass in healthy young adults. Material and methods: Thirty adults in their 20s without regular exercise habits completed a single-arm intervention in which they were instructed to walk ≥8,000 steps/day. Anthropometry, physical activity, dietary intake, fecal SCFAs, and gut microbiota composition were assessed before and after intervention. SCFAs were analyzed by gas chromatography, and microbiota by 16S rRNA sequencing. Results: Mean daily steps increased from 7,334 ± 1,939 to 8,344 ± 1,824 (p = 0.028). Total fecal SCFA concentrations rose significantly (4.50 ± 1.69 to 5.80 ± 2.37 μmol/g, p = 0.019), primarily due to acetate (2.20 ± 0.83 to 2.76 ± 1.33 μmol/g, p = 0.004). No significant changes were observed in propionate, n-butyrate, or the relative abundance of major butyrate-producing taxa. Skeletal Muscle Mass Index remained unchanged, and SCFA changes were not correlated with muscle mass. Conclusions: Increasing daily walking to approximately 8,000 steps elevates fecal SCFA production, particularly acetate, in healthy young adults but does not appear sufficient to promote short-term muscle mass gains. Integrating physical activity with dietary strategies that stimulate butyrate production may be necessary to optimize muscle health through the gut–muscle axis.